Simulated scenarios in nursing: an integrative literature review - Gustavo Correa de Amorim; Fabiana Cristina Pires Bernardinelli; Juliana da Silva Garcia Nascimento; Ingrid Fidelix de Souza; Divanice Contim; Suzel Regina Ribeiro Chavaglia (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to identify in scientific literature which simulated clinical scenarios were developed and validated for teaching and learning in nursing. Methods: integrative review, carried out in seven sources of information. The Rayyan program was used for selection, content analysis to explore the findings and the methodological assessment tool of the validity process, entitled Quality Appraisal tool for Validity Studies. Results: initially, 1,179 manuscripts were identified and 14 were part of the sample. Two categories were defined: Profile of simulated clinical scenarios produced in nursing; and Clinical skills developed and their assessment mechanisms. Final Considerations: there was a preponderance of high-fidelity scenarios, built in Brazil in the last five years, aimed at nursing students on the themes of emergency, maternal care and stomatherapy, addressing the assessment of cognitive, psychomotor and affective skills in nursing. Most studies obtained good methodological quality in their content validity process.